ANALISIS YURIDIS TINDAK PIDANA PEMBUNUHAN BERENCANA YANG DI LAKUKAN OLEH ANAK DI BAWAH UMUR - Turnip, Johannes Mangapul; Sagala, Juliana Priska Dewi; Sembiring, Hellen Br; Siburian, Sukses Marhasak Panungkunan (Ilmu Hukum Prima (IHP), 2024)
This research aims to juridical analysis of the crime of premeditated murder committed by a minor, with a focus on the study of the judge's decision. Committed by minors, with a focus on the study of the judge's decision. The research This research uses normative and empirical legal research methods by analyzing judges' decisions related to premeditated murder cases. Analyzing judges' decisions related to premeditated murder cases involving minors. cases involving minors. Through a normative approach, this research examines the legal framework governing juvenile criminal offenses, particularly in the context of premeditated murder. Children, especially in the context of premeditated murder. Meanwhile, the empirical approach involves analyzing judges' decisions to understand how these aspects of the law are applied in judicial practice. Aspects of the law are applied in judicial practice.